Relationship Between Drug Dreams, Affect, and Craving During Treatment for Substance Dependence. Issue 2 (March 2015) - Tanguay, Hélène; Zadra, Antonio; Good, Daniel; Leri, Francesco
<x xml:space="preserve">Abstract</x> Objectives: To explore the relationship between occurrence of drug dreams (DDs) and daytime negative affect and drug craving during the course of a 5-week treatment program for substance dependence. Methods: Using the dream journal methodology, 86 participants reported occurrence of dreams, dream content, and ratings of affect and drug craving. The relationships between the experience of DD, dream content ("active" vs "passive"), and affect and craving were analyzed using mixed model methods. Results: The experience of DD was associated with higher levels of negative affect (P < 0.001) and craving (P < 0.001). The occurrence of DD did not decrease significantly over the 5 weeks of the study. Cocaine/crack users reported a higher occurrence of DD (P < 0.05) than the other drug groups (opiates and alcohol), and DD involving "active" drug use was associated with larger (P < 0.05) changes in negative affect. Conclusions: These results are consistent with the hypothesis that DD can act as drug-conditioned stimuli to elevate negative affect and craving in abstaining individuals. Although correlational, such findings support the implementation of psychological and pharmacological interventions aimed at minimizing the impact of DD on individuals in recovery from drug addiction.